ISO standards in orthopaedics and traumatology - Shevchenko, Stanislav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The development of communications promotes a fruitful exchange of information about achievements in the countries. An obstacle to further progress is the absence of the single interpretation of the meaning of terms which are used in different parts of the world. In order to solve this problem, the world community has created an international standard organization (ISO). The technical committee ISO/TC 168 has worked out the standard ISO 21065:2017 «Prosthetics and orthotics. Conditions as for treatment and rehabilitation of patients after lower extremity amputation». In the third chapter the recommended terms and concepts are outlined. Introduction to this part of standard can improve mutual understanding between specialists.